Impact of Fiscal Capacity on the Convergence of Income Inequality in Russian Regions - Gasanov , Oscar S. (Economy of Regions, 2024)
At the regional level, the issue of income inequality in Russia remains relevant. Numerous studies on this topic do not fully reflect the efforts to overcome this problem in the context of budgetary policy. Meanwhile, monetary income of the population is greatly affected by budget support measures for regions. In this regard, it is necessary to assess the impact of fiscal capacity of regional budgets on the convergence of income inequality. In particular, the study examines the convergence of income inequality among the population of the Southern Federal District (SFD) of the Russian Federation. According to the hypothesis, fiscal expenditures per capita are one of the most important factors in the convergence of incomes at the regional level. The presence of unconditional and conditional convergence of income inequality for the period 2012–2021 was tested using the least squares method. Panel data with a one-period lag were assessed. Data of the Federal State Statistics Service of Russia on income inequality (the Gini index) and implementation of regional budgets in the Southern Federal District were used for modelling. The results indicate the presence of both unconditional and conditional convergence of income inequality in regions of the Southern Federal District. Two factors of fiscal capacity of regions were used for assessing the conditional convergence: estimated fiscal capacity and specific fiscal expenditures per capita of regions. It was established that the policy of budget equalisation of incomes remains a reliable tool for overcoming inequality in Russian regions. The findings can be used to solve the problems of regional inequality, implement fiscal federalism, plan budget expenditures for federal and regional budgets, as well as inter-budget transfers.